Analysis and chaos control of a four-dimensional magnetohydrodynamic model with hyperchaotic solutions - Daum, Hilson H. [UNESP]; Tusset, Angelo M.; Ribeiro, Mauricio A.; Litak, Grzegorz; Bueno, Atila M. [UNESP]; Balthazar, Jose M. [UNESP] (Springer Nature, 2021)
In this paper, the dynamical behavior of a four-dimensional magnetohydrodynamic model, consisting of a generalized Lorenz model, is investigated. A nonlinear dynamical analysis is performed using Lyapunov exponents and bifurcation diagrams, focusing on the chaotic and hyperchaotic behaviors associated with the bifurcation parameter (k1) that couples the equations of fluid displacement to the induced magnetic field. The State-dependent Riccati Equation (SDRE) and the Optimal Linear Feedback Control (OLFC) techniques are considered to design the state feedback control system that stabilizes the system to a previously defined orbit. The performance of the control systems are compared showing that the OLFC presents better results.
Keywords: Nonlinear dynamics; OLFC control; SDRE control